Mainstreaming Social Justice in Environmental Law Enforcement in Indonesia: Theories and Practices - Aji, Adiguna Bagas Waskito; Pramono, Setyo (Faculty of Law, Universitas Negeri Semarang, 2023)
This paper critically examines the convergence of environmental law enforcement and social justice within the context of Indonesia. Despite the nation's abundant biodiversity and natural resources, it grapples with the intricate challenge of harmonizing environmental conservation efforts with socio-economic development imperatives. However, the effective enforcement of existing environmental legislation often proves deficient, exacerbating environmental degradation and exacerbating social inequalities. Through an interdisciplinary lens drawing from law, sociology, and environmental studies, this study systematically investigates both the theoretical foundations and practical strategies for integrating social justice considerations into environmental law enforcement mechanisms. Central to the analysis is an exploration of principles such as equity, fairness, and inclusivity, elucidating pathways for their incorporation into the formulation and implementation of environmental regulations and enforcement protocols. Furthermore, the paper conducts a nuanced examination of the socio-political dynamics shaping the enforcement landscape in Indonesia, including power differentials, issues of corruption, and institutional capacities. Through a comprehensive review of pertinent literature and empirical case studies, the paper identifies promising approaches and best practices for enhancing social justice within environmental law enforcement. These encompass community-driven monitoring initiatives, robust stakeholder engagement mechanisms, and targeted capacity-building endeavors tailored to law enforcement agencies. Additionally, the paper underscores the transformative potential of technology and innovation in fostering greater transparency, accountability, and public participation in environmental governance processes. By synthesizing theoretical insights with empirical evidence, this paper contributes substantively to the nuanced understanding of the intricate interplay between environmental law enforcement and social justice within the Indonesian context.